Features of the recreational tourism development (on the example of the Republic of Tatarstan) - Ibragimova, Guliya Magdutovna; Gerkina, Elena Aleksandrovna (Revista Publicando, 2017)
Nowadays, a healthy lifestyle is being popularized; the government's goal is to reduce morbidity and mortality of the population, and simultaneously develop domestic tourism and the Republic in general. Tourism as an independent sphere of services presupposes the development of the region due to the influx of tourists and finances. These two factors together promote both recreational tourism, which contributes to the development of the Republic of Tatarstan as a tourist product, and the economic component of the region. It should be noted that the sanatorium and resort institution ceases to be a place of treatment and rest for the elderly and becomes a multifunctional health center designed for a wide range of consumers. Change in demand for health services is due to the fact that a healthy lifestyle comes into fashion. According to the socio-economic development strategy of the Republic of Tatarstan by 2030, one of the goals is to preserve public health and prolong longevity. Within the framework of this project it is planned to develop health tourism in the Republic.